Oral Hygiene Challenges Faced By Intellectually Disabled Patients - Laiba Khan; Absar Ur Rahman (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Historically, intellectual disability has been de- fined by significant cognitive deficits and adaptive behaviors along with deficits in functional and adaptive skills. Such individuals struggle to perform their day-to-day daily tasks without help and support. Similarly, these individuals are seen struggling to practice routine oral hygiene and face serious oral health issues. To counter that they seek help from dentists. Even for a dentist it is a real challenge when dealing with patients who suffer from intellectual disabilities, and there has been little discussion on how to overcome these.